Low-temperature atomic layer deposition as an advanced fabrication technique of semiconductor polymer materials - Chiappim, William [UNESP]; Botan Neto, Benedito Donizeti; Pessoa, Rodrigo Savio; Fraga, Mariana Amorim (Elsevier, 2024)
Atomic layer deposition (ALD) operating at low temperatures (25–100°C) has attracted growing interest in the surface modification of polymers and polymeric semiconductor materials. This technique offers remarkable potential for processing polymeric materials by providing precise control over the reaction between the ALD precursor and the polymeric substrate. Nevertheless, challenges persist owing to the diffusion and subsurface reaction exhibited by numerous polymers. These challenges arise from the diverse array of functional groups, surface morphology, structure, and internal bonds that modify the conditions of ALD deposition, resulting in dynamics of chemical reactions that require comprehension. This chapter provides an overview of the technological evolution of films deposited by ALD, emphasizing those deposited on polymeric materials. The state of the art of polymeric materials and the surface modification of polymers is presented. In addition, aspects of the equilibrium between reactant diffusion and the deposition surface reaction, which leads to a self-limiting half-reaction within a three-dimensional polymer, are detailed. This phenomenon is analogous to the self-limiting half-reaction observed during ALD on a solid planar substrate, and its implications are discussed.
Keywords: Atomic layer deposition; Infiltration; Low temperature; Polymers; Semiconductor